1989
DOI: 10.1111/j.1476-5381.1989.tb12604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bile acid on electrophysiological properties of rabbit sino‐atrial node in vitro

Abstract: Japan 1 In order to examine the action of bile acid on cardiac pacemaker activity, the effect of sodium taurocholate (NTC) was studied on the membrane potential and current of rabbit sino-atrial node preparations by means of a double microelectrode voltage clamp technique. 2 In spontaneously beating sino-atrial node preparations, NTC (above 30pM) decreased the maximum rate of rise of the action potential. Above 100yM, the compound also exerted a bradycardiac effect and decreased the rate of diastolic depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…This resulted in a slight but insignificant reduction in MAP, similar to recent findings from cirrhotic patients [14]. The decrease in DBP was not related to any impairment in the function of the myocardium or the sino-atrial node, as previously described for hydrophobic bile acids [15, 16]. The reduction in DBP may be caused either by a vasodilative effect of UDCA or by an impaired response to vasopressive mediators, as described for other bile acids like taurocholate [17, 18].…”
Section: Discussionsupporting
confidence: 73%
“…This resulted in a slight but insignificant reduction in MAP, similar to recent findings from cirrhotic patients [14]. The decrease in DBP was not related to any impairment in the function of the myocardium or the sino-atrial node, as previously described for hydrophobic bile acids [15, 16]. The reduction in DBP may be caused either by a vasodilative effect of UDCA or by an impaired response to vasopressive mediators, as described for other bile acids like taurocholate [17, 18].…”
Section: Discussionsupporting
confidence: 73%
“…This hypothesis was evaluated in one publication by Kotake et al [8] in which it was noted that bile acids affected the sinoatrial node by depressing node action potentials in a dose-related manner and producing a negative chronotropic effect which leads to bradycardia. In agreement with previous research results, another report indicated that taurocholate, another bile acid, caused a decrease in the rate of contraction of rat cardiomyocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has emerged to indicate that bile acids have arrhythmogenic potential [6,7]. It has been observed that increasing the concentration of bile acids alters the sinoatrial node and induces bradycardia [8]. This mechanism might explain acute fetal death because an association with a chronic cause, such as placental insufficiency, has not been demonstrated [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of BK Ca channels has been reported to control membrane potential and the degree of contraction and/or contractility in both vascular (Brayden and Nelson, 1992;Asano et al, 1993;Jaggar et al, 2000) and nonvascular (SuarezKurtz et al, 1991;Anwer et al, 1993) smooth muscle. Previous studies that showed bile acid-induced increases in K ϩ currents were performed in nonsmooth muscle preparations (Binah et al, 1987;Kotake et al, 1989;Devor et al, 1993). In particular, an increase in a Ca 2ϩ -sensitive conductance in colonic secretory cells by taurodeoxycholic acid led Dharmsathaphorn et al (1989) to postulate an involvement of Ca 2ϩ -dependent K ϩ channels in taurodeoxycholic acid effects on secretion in these cells.…”
Section: Possible Role Of Bile Acid Activation Of Bk Ca Channels In Bmentioning
confidence: 99%